Effect of Combination of Electrotherapy and Exercise Therapy on Functional Activities of Low Back Pain Patients - Nana Aulia Massakuta; Hendrik Hendrik; Yonathan Ramba (Humanistic Network for Science and Technology (HNST), 2022)
Low back pain is one of the main health problems experienced by humans. Microwave diathermy, bugnet exercise, and William flexion exercise are physiotherapy modalities that can be used to treat lower back pain, but their scientific effectiveness is uncertain. This study aims to evaluate the effect of pain reduction and degree of disability after being given a combination therapy of microwave diathermy, bugnet exercise, and William flexion exercise in patients with low back pain. This research was a pre-experimental study with a one-group pretest-posttest design which was carried out at dr. Tadjuddin Chalid Makassar with a population of 30 subjects who met the inclusion requirements. The sample was obtained by 26 subjects obtained using the Lemesow formula. Sampling was done by simple random sampling technique into one treatment group to measure the degree of disability using the Oswestry Disability Index (ODI) before and after the intervention. The results of data analysis with the Wilcoxon test obtained a pretest value of 39.80 + 4.64 and a posttest of 20.80 + 2.90 with a p-value of 0.005. Thus it can be concluded that the provision of Microwave diathermy, bugnet exercise, and william flexion exercise can have an effect on the functional activities of low back pain patients. Keywords: electrotherapy; exercise therapy; oswestry disability index; physiotherapy; low back pain